2009
DOI: 10.1002/jcb.22052
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of nuclear matrix proteins during the differentiation of human neuroblastoma SK‐N‐SH cells induced by retinoic acid

Abstract: To investigate the alteration of nuclear matrix proteins (NMPs) during the differentiation of neuroblastoma SK-N-SH cells induced by retinoic acid (RA), differentiation markers were detected by immunocytochemistry and NMPs were selectively extracted and subjected to two-dimensional gel electrophoresis analysis. Immunocytochemical observation demonstrated that the expression of neuronal markers was up-regulated in SK-N-SH cells following RA treatment. Meanwhile, 52 NMPs (41 of which were identified) changed sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Only a few short neurites were observable in control samples in comparison with cells treated with 1 µM ATRA (Figure 2b). Here, as expected from previous studies [49,50], a notable reduction in the total number of cells and a prevalence of cells with a globose cell body with numerous neurites was evident. logical differentiation, 10 randomly selected brightfield images were captured in at least three wells per condition after 5 days of incubation.…”
Section: Morphological Analysis and Cell Growth Assessmentsupporting
confidence: 89%
“…Only a few short neurites were observable in control samples in comparison with cells treated with 1 µM ATRA (Figure 2b). Here, as expected from previous studies [49,50], a notable reduction in the total number of cells and a prevalence of cells with a globose cell body with numerous neurites was evident. logical differentiation, 10 randomly selected brightfield images were captured in at least three wells per condition after 5 days of incubation.…”
Section: Morphological Analysis and Cell Growth Assessmentsupporting
confidence: 89%
“…In our previous study, we found NPM was a nuclear matrix protein and its expression was downregulated in the induced differentiation of human osteosarcoma, human neuroblastoma tumors and human liver cancer (6)(7)(8), indicating NPM functioned in regulating the differentiation of tumor cells (9). Liver cancer is the most common malignant gastrointestinal cancer and the screening for functional proteins related to liver tumor cell differentiation will contribute to the elucidation of the mechanism of liver cancer development and its early diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study has found an aberrant expression of hnRNP A2/B1 in nuclear matrix‐intermediate filament system during the induced‐differentiation of human osteosarcoma MG‐63 cells and human neuroblastoma SK‐N‐SH cells, suggesting that hnRNP A2/B1 is closely related with the proliferation and differentiation of human neuroblastoma SK‐N‐SH cells [Zhao et al, 2008; Liang et al, 2009]. Therefore in this study, retinoic acid (RA), a classical inducer [Liang et al, 2009; Tonge and Andrews, 2010], was used to induce human neruoblastoma SK‐N‐SH cells into differentiation. We investigated the distribution and expression of hnRNP A2/B1 in the nuclear matrix, and primarily explored the relationship of hnRNP A2/B1 with related oncogenes and tumor suppressor genes.…”
mentioning
confidence: 99%